A Case Study on the Application of Geographic Information System (GIS) to the Analysis and Transformation of Archives in the Qing Dynasty into Audio-visual Works: Taking the Making of an Archive Documentary in the Qing Dynasty by the National Palace Museum as an Example - Shao-Chun Wu (Tūzī yǔ dàng’àn xuékān, 2022)
Because archives contain a lot of time and space information, it is difficult to display them in words, and it is difficult to describe them layer by layer on printed boards. However, after the introduction of GIS, the relationship between time and space can be presented visually. Over the years, the digital humanity research results with the application of GIS containing a large amount of analytical information, charts, and layer concepts often lack the appeal to the general public when displayed in exhibitions. Due to the popularity of streaming videos and the fact that the general public is increasingly accustomed to absorbing audio-visual materials, there is an urgent need for cultural institutions to transform such research results into audio-visual works with visual impacts to enhance public absorption. This study takes the documentary video “Impressions of Sazum” filmed by the National Palace Museum as the case to analyze how the Museum applied GIS to explore the process of the Governor of Fujian and Zhejiang came to Taiwan for the inspection of Sazum (now Sun Moon Lake) during the Daoguang period of the Qing Dynasty and wrote the memorial to the throne. The results of the Museum’s study were transformed into an audio-visual work with visual language as the main appeal. Lastly, this study proposes several suggestions for museums and archives to apply GIS in the studies of archives and the production of audio-visual works.